PERANCANGAN SISTEM TRANSAKSI ONLINE PEMERIKSAAN ANTI SARS-COV2 BERBASIS WEB - Sulistiono Sulistiono; Atang Susila (Jurnal Informatika Universitas Pamulang, 2022)
The biomedical clinic laboratory is a laboratory that is engaged in the health sector. (1) Currently all institutions engaged in the health sector are struggling to deal with a covid-19 virus, the virus can spread quickly just by passing each other and even crowding. To detect the virus, the biomedical clinic laboratory has an examination called Anti-SARS-CoV-2 where the examination has a blood sample collection method that must comply with the health protocol that has been disseminated by the health office. The problem currently being faced is the transaction process which gives concern about the current pandemic period because the anti-SARS-Cov2 registration process is carried out face-to-face, not using an online transaction system. (2) The method used by the author is the RAD (rapid application development) method. For the convenience of patients, the biomedical clinic laboratory management makes a special online registration for patients who want to check Anti-SARS-CoV-2 where patients can visit the web that has been set by the biomedical clinic laboratory. This web-based Anti-SARS-CoV-2 inspection online transaction system was created using the PHP programming language using the codigniter framework. (3) This system processes patient data from patient registration to the issuance of examination results. Of course, this system can provide patient comfort, because patients have maintained the health protocol because they do not pass each other for too long with the registration officer and this system has a home service schedule where patients can choose to take blood at home so they don't run into more people. (4) Development of the Anti-SARS-CoV-2 inspection registration application into a mobile application so that it can be easily accessed or anywhere, adding automatic or scheduled data backup features so that data is maintained in case of damage to the server or network and avoids human error, because currently backup data can only be backed up if the admin clicks the data backup menu.